Optimalisasi Media Sosial untuk Pendidikan Berkarakter : Peluang dan Tantangan Bagi Generasi Muda Menuju Generasi Emas Indonesia - Rohman, Slamet Fatkhur (Economie: Jurnal Ilmu Ekonomi, 2025)
Today's young generation is one of the users of internet-based technology. The availability of this technology means we can connect to social media, which has now become an addiction for the younger generation. The addiction makes them want to stay on social media for a long time using the technological devices they own. Social media that is often used includes WhatsApp, Instagram, X, TikTok, Facebook, and others. By combining evidence from research, personal correspondence and book sources, this research shows that social media can be an opportunity but also a challenge for the younger generation in order to form character education towards Indonesia's golden generation. In conclusion, social media is an effective tool in forming character education so that the younger generation has high integrity, responsibility and is ready to face future challenges.